¿A container yard, in the oriente antioqueño? - Ceballos - Ramírez, Silvia Liliana; Guisao - Giraldo, Érica Yaneth (Universidad Francisco de Paula Santander, 2020)
The use of the cargo container since the decade of fifties has generated changes in the mobilization of the load. As a result of the trips of the container ships, the construction of container yards or dry ports begins, which gain importance every day in the logistics processes. The purpose of this script is to show whether a dry port in Eastern Antioquia in the Altiplano subregion, would contribute to the efficiency of foreign trade processes.  The investigation type was mixed, conclusive and analytical; Interviews were managed with three (3) container yards located in the department of Antioquia, and surveys were conducted with 63 companies located in the region that carry out import, export or both operations. It is highlighted that entrepreneurs are considering that the opening of a yard could reduce costs and operating times and be able to negotiate better rates with shipping companies and land transport companies.